Recent Insights Into Molecular Mechanisms of Propofol-Induced Developmental Neurotoxicity: Implications for the Protective Strategies. (November 2016) - Bosnjak, Zeljko J.; Logan, Sarah; Liu, Yanan; Bai, Xiaowen
Abstract : Mounting evidence has demonstrated that general anesthetics could induce developmental neurotoxicity, including acute widespread neuronal cell death, followed by long-term memory and learning abnormalities. Propofol is a commonly used intravenous anesthetic agent for the induction and maintenance of anesthesia and procedural and critical care sedation in children. Compared with other anesthetic drugs, little information is available on its potential contributions to neurotoxicity. Growing evidence from multiple experimental models showed a similar neurotoxic effect of propofol as observed in other anesthetic drugs, raising serious concerns regarding pediatric propofol anesthesia. The aim of this review is to summarize the current findings of propofol-induced developmental neurotoxicity. We first present the evidence of neurotoxicity from animal models, animal cell culture, and human stem cell–derived neuron culture studies. We then discuss the mechanism of propofol-induced developmental neurotoxicity, such as increased cell death in neurons and oligodendrocytes, dysregulation of neurogenesis, abnormal dendritic development, and decreases in neurotrophic factor expression. Recent findings of complex mechanisms of propofol action, including alterations in microRNAs and mitochondrial fission, are discussed as well. An understanding of the toxic effect of propofol and the underlying mechanisms may help to develop effective novel protective or therapeutic strategies for avoiding the neurotoxicity in the developing human brain. Abstract : Published ahead of print August 22, 2016.